Paciente de sexo femenino de 43 años de edad con glioblastoma y obesidad grado 3. - Escobar Manzo, Ariel Moisés (2021)
The present clinical case is base don a 43-year-olg female patient who attended the medical consulation due to asthenia, excess weight, depression, and glioblastoma, she refers, having a personal pathological history of hypertension and diabetes, does not smoke or drink alcohol. On clinical examination, patient, has a picnic biotype, no palpable cervical lynphadenopathy, chest: ventilated csps, rhythmic rscs, voluminous abdomen, obtuse sterno-costal angle, abundant adipose tissue especially in the tympanic belly, active bowel sounds, los of facial hair and in the head, there are no edema in the lower extremities, or inguinal adenopathy, dry skin, fold sign, normal erectories, 97% saturation, temperatura 36.4C and blood pressure 90/60 mmHg. An anthropometric evaluation is carried out: a weight of 95 kg and a height of 153cm. Abdominal circumference 122 cm, arm circumference 33c, calf circumference 36cm.